Economic Development and Maine’s Sustainability Solutions Initiative - Noblet, Caroline; Bell, Kathleen; Colgan, Charles; Teisl, Mario (Maine Policy Review, 2012)
The authors discuss how Maine’s Sustainability Solutions Initiative (SSI) can contribute to economic development in the state. SSI research is covering five of the seven targeted technology areas identified in recent reports as being important for economic development in the state (forestry and agriculture, environmental, information, composites, marine and aquaculture). The authors note how the broad scope of research carried out through SSI provides opportunities to catalyze new commercial opportunities. As important, SSI is providing many students with a unique learning environment that will prepare them for the new knowledge-based economy.
Keywords: Maine; economic development; sustainability